1998
DOI: 10.1111/j.1528-1157.1998.tb05150.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutional Changes and Outcome of West Syndrome: Correlation with Magnetic Resonance Imaging Findings

Abstract: Summary:The prognosis and evolutional changes of 77 patients with West syndrome (WS) were studied after patients were classified into four groups op the basis of their magnetic resonance imaging (MRI) findings: anomaly, perinatal injury, normal, and the other groups. The average age at onset of spasms was earliest in the patients with anomalies and latest in patients with normal MRI findings. Patients with normal MFU findings had the shortest duration of spasms, and patients with anomalies had the longest dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Cranial MRI has a distinctive place in etiologic diagnosis in IS. A differentiation in prognostic consequences depending on the type of brain lesion was reported, and the best prognosis was attributed to the group with normal cMRI findings (24).…”
Section: Discussionmentioning
confidence: 99%
“…Cranial MRI has a distinctive place in etiologic diagnosis in IS. A differentiation in prognostic consequences depending on the type of brain lesion was reported, and the best prognosis was attributed to the group with normal cMRI findings (24).…”
Section: Discussionmentioning
confidence: 99%
“…This increased survival rate has been associated with a concomitant increase in the prevalence of WS . Because perinatal factors are relatively frequent and potentially preventable, they are particularly important in the etiology of WS …”
Section: Discussionmentioning
confidence: 99%
“…Prognostic differences in accordance with the type of brain lesions have been reported by Okumura et al in their study on 77 patients with infantile spasms that revealed a 31% incidence of normal cranial MRIs. 6 In our study, in which 25.5% (22 cases) of patients had normal cranial MRIs, 14 of them (63.6%) were diagnosed as symptomatic infantile spasms. A specific etiology could be determined in only 2 patients (2/14; 14%) with symptomatic infantile spasms and normal cranial MRIs; this proportion in the total group of patients, however, was 74% (64 cases).…”
Section: Discussionmentioning
confidence: 53%